Analisis Pengaruh Penggunaan Gadget terhadap Tingkat Konsentrasi Siswa-Siswi Kelas VI SD Siti Aminah Surabaya - Rizki Ramadhan; Diva Cahya Nirwana; Salsabilla Dwi Clarissa; Ayu Wulandari (Jurnal Pendidikan Tambusai, 2025)
Rapid digital technology growth has integrated gadgets into elementary students' daily routines, raising concerns about concentration amid rising screen time post-COVID-19, particularly at SD Siti Aminah Surabaya where sixth-grade students face academic pressures. This study aims to analyze gadget use's influence on their learning concentration. Employing a quantitative survey design, the population comprised all 30-35 sixth-grade students, with a purposive sample of 25 selected for accessibility and relevance. Data were collected via validated Likert-scale questionnaires measuring gadget frequency/duration and concentration indicators, analyzed using SPSS for simple linear regression including F-test, t-test, R, and R Square. Results indicate no significant influence, with R=0.031, R Square=0.001, F=0.021 (Sig.=0.887), and t=-0.144 (Sig.=0.887), all exceeding 0.05, showing very weak correlation. In conclusion, other factors like environment and supervision dominate, recommending controlled gadget policies for optimal learning.